2007
DOI: 10.1159/000101914
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lesion Characteristics and Mineralising Solution Type on Enamel Remineralisation in vitro

Abstract: The aim was to study the effect of lesion preparation technique and solution composition on remineralisation of artificial lesions in vitro. Lesions were prepared with similar total mineral loss, but different mineral distribution, i.e., low (14.0) or high R (34.8) values. Lesions from both groups were remineralised (10 days, 37°C) in two different solutions, with similar supersaturation with respect to hydroxyapatite (St), but calcium:phosphate ratios representing either hydroxyapatite stoichiometry or plaque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
1
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 29 publications
5
52
1
5
Order By: Relevance
“…These lesions showed considerable differences in their respective mineral distributions (Fig. 1) -MeC were more demineralized closer to the lesion surface and therefore more easily remineralized, which is in agreement with findings by Lynch et al [35]. Naturally, this all begs the question what resembles most closely a clinically relevant lesion -all three lesion protocols are justifiable, but do they mimic in vivo caries lesions?…”
Section: Discussionsupporting
confidence: 89%
“…These lesions showed considerable differences in their respective mineral distributions (Fig. 1) -MeC were more demineralized closer to the lesion surface and therefore more easily remineralized, which is in agreement with findings by Lynch et al [35]. Naturally, this all begs the question what resembles most closely a clinically relevant lesion -all three lesion protocols are justifiable, but do they mimic in vivo caries lesions?…”
Section: Discussionsupporting
confidence: 89%
“…Regardless, MeC and CMC results are in disagreement with a recent in situ study, 6 reporting that under virtually identical conditions and in the presence of F, high-R lesions remineralize and low-R lesions further demineralize. Furthermore, Lynch et al 5 reported that high-R lesions are more responsive to remineralizing treatments than low-R lesions because of the high-R lesions' greater porosity. High-and low-R lesions were somewhat comparable between all studies, although different protocols were used for low-R lesion creation in the present study, which is unlikely to be accountable for the observed discrepancy.…”
Section: 2)mentioning
confidence: 99%
“…Unlike DZ base effects, which are comparatively well understood, the effect of R value has been studied to far lesser extent as the majority of investigators concentrate only on one (preferred) lesion type. Nonetheless, Lynch et al 5 found that high-R lesions are more responsive to remineralizing treatments than low-R lesions, presumably due to the high-R lesions' greater porosity. A very recent in situ study 6 found that, rather surprisingly, high-and low-R lesions showed opposite behaviours under virtually identical conditions, with the high-R lesions exhibiting some remineralization, whereas low-R lesions further demineralized.…”
Section: Introductionmentioning
confidence: 99%
“…Amostras de esmalte bovino são geralmente expostas a soluções ou géis desmineralizantes compostos por ácido acético ou lático (pH entre 4,5-5,0) subsaturados em relação à apatita, simulando parcialmente as condições do fluído do biofilme e consequentemente, permitindo a formação de lesão de cárie inicial (não cavitada) DUIJSTERS, 1982;EDGAR, 1983;BUSKES;ARENDS, 1985;WHITE, 1987;TEN CATE et al, 1996;KIELBASSA et al, 2005;MONY;TEN CATE, 2007;QUEIROZ et al, 2008; MAGALHÃES et al, 2009, HUANG, 2010.…”
Section: Quadrosunclassified
“…Modelos in vitro para a produção de lesões cariosas em esmalte são capazes de simular a dinâmica da perda e ganho mineral, com vantagens como a padronização, rapidez e facilidade. Estes modelos permitem o melhor entendimento da interação entre a desmineralização e remineralização e sobre os fatores que podem afetar estes processos, como o fluoreto (WHITE, 1995).Amostras de esmalte bovino são geralmente expostas a soluções ou géis desmineralizantes compostos por ácido acético ou lático (pH entre 4,5-5,0) subsaturados em relação à apatita, simulando parcialmente as condições do fluído do biofilme e consequentemente, permitindo a formação de lesão de cárie inicial (não cavitada) DUIJSTERS, 1982;EDGAR, 1983;BUSKES;ARENDS, 1985;WHITE, 1987;TEN CATE et al, 1996;KIELBASSA et al, 2005;MONY;TEN CATE, 2007;QUEIROZ et al, 2008; MAGALHÃES et al, 2009, HUANG, 2010.Diferenças entre estas soluções ou géis em relação ao grau inicial de saturação de minerais, concentração de fluoreto, tipo de ácido e viscosidade podem resultar em diferenças consideráveis nas características físicas e mecânicas do tecido dentário desmineralizado, Portanto, o objetivo deste presente estudo foi avaliar o efeito do tipo de lesão cariosa artificial produzida por diferentes protocolos in vitro em relação ao potencial remineralizante da saliva humana apenas e na presença do dentifrício fluoretado (aplicação caseira do fluoreto) e do verniz (aplicação profissional de fluoreto) + dentifrício fluoretado in …”
unclassified